Combretum lanceolatum flowers ethanol extract inhibits hepatic gluconeogenesis: an in vivo mechanism study - Siqueira, Juliany Torres; Batistela, Emanuele; Pereira, Mayara Peron; da Silva, Virginia Claudia; de Sousa Junior, Paulo Teixeira; Andrade, Claudia Marlise Balbinotti; Kawashita, Nair Honda; Bertolini, Gisele Lopes; Baviera, Amanda Martins [UNESP] (Taylor & Francis, 2016)
Context Ethnopharmacological studies have demonstrated that plants of the Combretum genus presented antidiabetic activity, including Combretum lanceolatum Pohl ex Eichler (Combretaceae). Objective This study investigated the hepatic mechanisms of action of C. lanceolatum flowers ethanol extract (ClEtOH) related to its antihyperglycaemic effect in streptozotocin-diabetic rats. Materials and methods Male Wistar rats were divided into normal (N) and diabetic control (DC) rats treated with vehicle (water); diabetic rats treated with 500 mg/kg metformin (DMet) or 500 mg/kg ClEtOH (DT500). After 21 d of treatment, hepatic glucose and urea production were investigated through in situ perfused liver with l-glutamine. Changes in the phosphoenolpyruvate carboxykinase (PEPCK) levels and in the activation of adenosine monophosphate-activated protein kinase (AMPK) and insulin-signalling intermediates were also investigated. Results Similar to DMet, DT500 rats showed a reduction in the rates of hepatic production of glucose (46%) and urea (22%) in comparison with DC. This reduction was accompanied by a reduction in the PEPCK levels in liver of DT500 (28%) and DMet (43%) when compared with DC. AMPK phosphorylation levels were higher in the liver of DT500 (17%) and DMet (16%) rats. The basal AKT phosphorylation levels were increased in liver of DT500 rats, without differences in the insulin-stimulated AKT phosphorylation and in the insulin receptor levels between DC and DT500 rats. Discussion and conclusion The antidiabetic activity of ClEtOH can be attributed, at least in part, to inhibition of hepatic gluconeogenesis, probably due to the activation of both AMPK and AKT effectors and reduction in the PEPCK levels.
Keywords: Antidiabetic activity; glucose hepatic production; phosphoenolpyruvate carboxykinase